Empirical study about the role of social networks in SME performance. Issue 4 (14th November 2016) - Franco, Mário; Haase, Heiko; Pereira, Ana
Abstract : Purpose: This study aims to show the role of social networks in the performance of small- and medium-sized firms (SMEs) in an inland region of Portugal. The main objective is to ascertain the motives for adhering to social networks and to understand if this type of network influences performance in this firm sector. Design/methodology/approach: To fulfill this aim, a quantitative research was adopted, based on application of a questionnaire, the final sample being formed of 86 SMEs. Findings: Based on the results obtained, it is concluded that the SMEs studied are connected to social networks, especially Facebook. The principal reason for this type of firm connecting to social networks has to do with the possibility of presenting services to a greater number of potential customers. Practical implications: The empirical evidence obtained also shows that the motives associated with cost reduction influence both financial indicators (profit growth) and non-financial indicators (human resource results), and communication and innovation influence only non-financial performance (level of satisfaction). Originality/value: This study contributes to advancing theory in the field of social networks in SMEs. More precisely, this study suggests that to assess their performance, SME leaders should not use only measures of a financial nature (sales volume, level of growth, etc.), but rather in combination with non-financial indicators such as customer satisfaction, reputation and others.